The transforming potential of the c-erbB-2 protein is regulated by its autophosphorylation at the carboxyl-terminal domain. - Akiyama, T (1991)
The mutant c-erbB-2 protein with Glu instead of Val-659 exhibited transforming activity in NIH 3T3 cells. This protein showed enhanced tyrosine kinase activity in vitro and enhanced autophosphorylation at Tyr-1248 located proximal to the carboxyl terminus. Enhanced tyrosine phosphorylation of several cellular proteins was detected in cells expressing the Glu-659 c-erbB-2 protein. Introduction of an additional mutation at the ATP-binding site (Lys-753 to Met) of this protein resulted in abolition of its transforming ability. These data indicate that the transforming potential of c-erbB-2 is closely correlated with elevated tyrosine kinase activity of the gene product. To investigate the role of autophosphorylation in cell transformation, we introduced an additional mutation at the autophosphorylation site of the Glu-659 c-erbB-2 protein (Tyr-1248 to Phe). This mutant protein exhibited lower tyrosine kinase activity and lower transforming activity. On the other hand, when the carboxyl-terminal 230 amino acid residues were deleted from the c-erbB-2 protein, the tyrosine kinase activity and cell-transforming activity of the protein were enhanced. Thus, the carboxyl-terminal domain, which contains the major autophosphorylation site, Tyr-1248, may regulate cellular transformation negatively and autophosphorylation may eliminate this negative regulation.